LITERASI TEKNOLOGI DALAM PERSPEKTIF CALON PENDIDIK SEKOLAH DASAR: SEBUAH ANALISIS KEBUTUHAN - Nina Suzanne (JMIE (Journal of Madrasah Ibtidaiyah Education), 2019)
4.0 era is characterized by the use of massive and critical technology. Almost everyone has smartphone with 4G internet connection for communication and having information around the world rapidly. Students also get the advantage to do their assignment, get more interactive media for learning, or just for fun in social media. However, negative impact cannot be avoided if the students do not understand how to use the technology wisely. Therefore, technology literacy is needed to give the students strong basis in using technology to support their activities. This research aims to describe students’ perception toward the importance of technology literacy for students and candidate teachers. The informants were 23 PGMI students of IAIN Batusangkar who were given open-ended questionnaire about their perspective on the use of technology in teaching and learning process. The results describe that the use of technology such as smartphone wisely with a good knowledge on it is a must. Being innovative, creative, and dynamic are expected from students and candidate teachers as well.